IDENTIFIKASI VIRUS PENYAKIT JEMBRANA PADA SAPI BALI MENGGUNAKAN POLYMERASE CHAIN REACTION (PCR) DI PROVINSI KEPULAUAN BANGKA BELITUNG - Riko Irwanto; Correy Wahyu Adi Sulistyo; Ari Ari; Aditya Jeffri Irawan (BERITA BIOLOGI, 2021)
Bali cattle is one of the typical Indonesian livestock that is widely cultivated because of its high reproductive and adaptation capabilities to the environment. However, behind these advantages, bali cattle have a weakness, namely they are susceptible to the jembrana virus which can cause jembrana disease. This disease will cause a decrease in the immune system of bali cattle so that they are susceptible to other diseases that will lead to the death of the cattle. The method used in the identification of the Jembrana disease virus is the Polymerase Chain Reaction-Reverse Transcription (PCR-RT) technique. Identification do 10 Bali cows in Panca Tunggal Village, South Bangka Regency and 11 Bali cattle in Temberan Village, Pangkalpinang City. The bali cattle serum used for virus identification was centrifuged to obtain buffycoat. The PCR-RT technique is carried out in several stages, namely sampling, buffycoat making, extraction, master mix making, amplification, agar manufacture, electrophoresis and visualization. Based on the test, it was found that A1 and A2 bali cattle from Panca Tunggal Village, South Bangka Regency indicated the presence of the Jembrana virus. So that this Polymerase Chain Reaction Technique can help detect the presence of the Jembrana virus in bali cattles.